An introduction to electrospinning and nanofibers - Ramakrishna, Seeram (World Scientific, 2005)
The research and development of nanofibers has gained much prominence in recent years due to the heightened awareness of its potential applications in the medical, engineering and defense fields. Among the most successful methods for producing nanofibers is the electrospinning process. In this timely book, the areas of electrospinning and nanofibers are covered for the first time in a single volume. The book can be broadly divided into two parts: the first comprises descriptions of the electrospinning process and modeling to obtain nanofibers while the second describes the characteristics and a.